Influence of the off-great-circle propagation of Rayleigh waves on event-based surface wave tomography in Northeast China. Issue 2 (7th May 2018) - Chen, Haopeng; Ni, Sidao; Chu, Risheng; Chong, Jiajun; Liu, Zhikun; Zhu, Liangbao
SUMMARY: Surface waves are generally assumed to propagate along the great-circle paths in most of the surface wave tomographies. However, when lateral heterogeneity is strong, the off-great-circle propagation may occur and deteriorate surface wave tomography results based on the great-circle assumption. In this study, we used teleseismic waveforms recorded by the NorthEast China Extended SeiSmic Array in Northeast China to study the off-great-circle propagation of Rayleigh waves using the beamforming method and evaluated the influence of the off-great-circle propagation on event-based surface wave tomography. The results show that arrival angle anomalies generally increase with decreasing period. The arrival angle anomalies at 60 and 50 s periods are smaller than that at 40 and 30 s periods, which indicates that the off-great-circle propagation is relatively weak for longer periods. At 30 s period, the arrival angle anomalies are relatively larger and some of the measurements can exceed 20°, which represents a strong off-great-circle propagation effect. In some areas, the arrival angle anomalies of adjacent events differ significantly, which may be attributed to multipathing propagation of surface waves. To evaluate the influence of the off-great-circle propagation on event-based surface wave tomography, we used measured arrival angle anomalies to correct two-station phase velocity measurements, and performed azimuthal anisotropy tomography using dispersion data sets with and without the arrival angle correction. At longer periods, such as 60 s, the influence of the off-great-circle propagation on surface wave tomography is weak, even though the corrected model has better data fit than the uncorrected model. However, the influence of the off-great-circle propagation is non-negligible at short periods. The tomography results at 30 s period show that the differences in phase velocity, the strength of anisotropy and the fast direction can be as large as 1.5, 1.0 per cent and 30°, respectively. Furthermore, the corrected phase velocity is systematically lower than that without correction. This study illustrates the necessity of studying the off-great-circle propagation of surface waves to improve the accuracy of event-based surface wave tomography, especially for shorter periods.